2021
DOI: 10.1186/s12913-021-06379-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in factors influencing maternal health service use in Jimma Zone, Ethiopia: a geographically-weighted regression analysis

Abstract: Background Persisting within-country disparities in maternal health service access are significant barriers to attaining the Sustainable Development Goals aimed at reducing inequalities and ensuring good health for all. Sub-national decision-makers mandated to deliver health services play a central role in advancing equity but require appropriate evidence to craft effective responses. We use spatial analyses to identify locally-relevant barriers to access using sub-national data from rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Sufficient studies leverage spatial and spatio-temporal methods as indispensable tool for identifying inequalities in access for maternal health services and disparities in utilization 31 . Classical statistical algorithms such as Spatial autocorrelation 32 , Geographically weighted regression 33 , Local Indicators of Spatial Autocorrelation 34 have been employed frequently for understanding maternal health and MMR integrated through panel data models in China, Ethiopia and fifty four (54) African countries respectively. Inverse distance weighted method of interpolation method has been used to assess spatial patterns of maternal mortality in Tanzania 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient studies leverage spatial and spatio-temporal methods as indispensable tool for identifying inequalities in access for maternal health services and disparities in utilization 31 . Classical statistical algorithms such as Spatial autocorrelation 32 , Geographically weighted regression 33 , Local Indicators of Spatial Autocorrelation 34 have been employed frequently for understanding maternal health and MMR integrated through panel data models in China, Ethiopia and fifty four (54) African countries respectively. Inverse distance weighted method of interpolation method has been used to assess spatial patterns of maternal mortality in Tanzania 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study on the determinants of antenatal care utilization in India found spatial dissimilarities in ANC utilization by women and a moderate spatial autocorrelation (Moran’s I = 0.6210) confirmed the spatial dependence of ANC [ 21 ]. A few other studies have also observed significant spatial heterogeneity in ANC [ 22 , 23 ], institutional delivery [ 24 ], and PNC [ 25 27 ]. Studies have also observed that home delivery after ANC was spatially clustered [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%